2020
DOI: 10.1016/j.jocs.2020.101157
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing, Modeling, and Accurately Simulating Power and Energy Consumption of I/O-intensive Scientific Workflows

Abstract: While distributed computing infrastructures can provide infrastructure-level techniques for managing energy consumption, application-level energy consumption models have also been developed to support energy-efficient scheduling and resource provisioning algorithms. In this work, we analyze the accuracy of a widely-used application-level model that has been developed and used in the context of scientific workflow executions. To this end, we profile two production scientific workflows on a distributed platform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Three main components contribute to the energy consumption in the Edge-DCs: the compute nodes, the switches and the cooling system. The power consumption of a compute node is made up of two terms: a static consumption that accounts for the power consumed when the server is powered on but not running any load or running background activities, and a dynamic consumption that depends linearly on the CPU frequency and the nature of the compute load [30]. Adelin et al [31] showed that a switch consumes more than 80% of its nominal power when it is switched on, including when there is no traffic (static state).…”
Section: A Edge-data Centers Power Consumptionmentioning
confidence: 99%
“…Three main components contribute to the energy consumption in the Edge-DCs: the compute nodes, the switches and the cooling system. The power consumption of a compute node is made up of two terms: a static consumption that accounts for the power consumed when the server is powered on but not running any load or running background activities, and a dynamic consumption that depends linearly on the CPU frequency and the nature of the compute load [30]. Adelin et al [31] showed that a switch consumes more than 80% of its nominal power when it is switched on, including when there is no traffic (static state).…”
Section: A Edge-data Centers Power Consumptionmentioning
confidence: 99%
“…In [40], [41], we have proposed and validated a power consumption model that accounts for CPU utilization, computations that execute on multi-core compute nodes, and I/O operations (including the idle power consumption caused by waiting for these operations to complete). In this work, we leverage this model, to estimate the energy consumption of the execution of large-scale workflows.…”
Section: Case Study: Estimating Energy Consumption Of Large-scale Wor...mentioning
confidence: 99%
“…When such workflows are executed over large amounts of data, their runtimes can easily exceed days or even weeks [2,8,26,27]. To effectively use the available cluster resources, many workflow management systems have a scheduling component [6,12,24,31] that determines which tasks are executed when and on which of the available nodes to achieve some optimization goal, such as wallclock-time.…”
Section: Introductionmentioning
confidence: 99%